2008
DOI: 10.1063/1.2957987
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fine roughness of insulator surface on threshold voltage stability of organic field-effect transistors

Abstract: We have investigated the influence of the surface roughness of an insulator on the threshold voltage shift caused by gate bias stressing in organic field-effect transistors (OFETs). Our investigation was conducted for OFETs with SiO2 insulators. We observed that the threshold voltage shift is extremely sensitive to changes in the fine roughness of the SiO2 surface; the shift increased with the roughness. The large shift in OFETs with rough SiO2 insulators can be attributed to lattice distortion in pentacene la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 27 publications
0
28
1
Order By: Relevance
“…This is diametrically opposed to Ref. [25], in which the authors reported the significant decrease in the grain size in the pentacene film with an increase in the surface roughness (from 0.16 to 0.22 nm) of the underlying insulator, indicating that the sub-nanometer-scale surface roughness of the underlayer is even detrimental to the subsequent growth of pentacene molecules. However, the monolayer coverage of pentacene grains on the relatively rough Type II adhesion layer was substantially larger than that on Type I adhesion layer, which follows preferably the observed surface energy variation.…”
Section: Resultscontrasting
confidence: 59%
“…This is diametrically opposed to Ref. [25], in which the authors reported the significant decrease in the grain size in the pentacene film with an increase in the surface roughness (from 0.16 to 0.22 nm) of the underlying insulator, indicating that the sub-nanometer-scale surface roughness of the underlayer is even detrimental to the subsequent growth of pentacene molecules. However, the monolayer coverage of pentacene grains on the relatively rough Type II adhesion layer was substantially larger than that on Type I adhesion layer, which follows preferably the observed surface energy variation.…”
Section: Resultscontrasting
confidence: 59%
“…Likewise, the chemical and morphological properties of a gate insulator are deemed decisive to the field-effect mobility in bottom-gate organic TFTs by influencing the crystalline growth of an organic semiconductor. Several works have shown that the rough surface of a gate insulator causes a reduction in the field-effect mobility [5,8]. In contrast, recent studies reported that the crystalline growth of organic semiconductors and the performance of organic TFTs can be improved by introducing structured morphologies on the surface of a gate insulator [9,10], which motivates our research into cowl-shaped nanostructures for application in organic TFTs.…”
Section: Introductionmentioning
confidence: 88%
“…It is envisaged that they will have enormous market in a wide range of applications, for example as the driving elements for flexible displays, radio-frequency identification tags and large area sensors [1][2][3]. Previous investigations on organic TFTs have focused on materials [4], interfacial properties [5], source/drain contact engineering [6] and processing techniques [7], to enhance the TFT performance. Among the characteristic parameters, the field-effect mobility is known to be greatly influenced by the deposition conditions and consequent crystallinity of organic semiconductors.…”
mentioning
confidence: 99%
“…Therefore, the characteristics of OFETs are strongly influenced by the characteristics of the insulator surface [9][10][11]. From this point of view, we have examined the time variation of the source-drain current of OFETs when the chemical species of the insulator surface can change the conformational structure.…”
mentioning
confidence: 99%